Palladium-Catalyzed Annulation of Tertiary Anilines with 3‑Butenoic Acid via Dual C–H Bond Activation - Zhang, Jinhui; Liu, Chao; Wu, Jiahao; Tan, Xiangwen; Wu, Wanqing; Jiang, Huanfeng (Organic letters, 2024)
Catalytic cyclization via dual C–H bond activation has evolved as a powerful strategy for building bi- and polycyclic molecules. Herein, a palladium-catalyzed annulation of tertiary anilines with 3-butenoic acid via N-α-C(sp3)–H and ortho-C(sp2)–H activation is described. The remarkable characteristics of this reaction include excellent diastereoselectivity, broad substrate scope, and good tolerance for some highly sensitive groups. In addition, the KIE experiment suggested that the C–H bond abscission is not the turnover-limiting step.